Europejski Fundusz Społeczny jako instrument aktywizacji zawodowej osób niepełnosprawnych w Polsce w latach 2004-2006 - Barabasz, Adam (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The European Social Fund is one of the instruments used to prevent the unemployment of people with disabilities in Poland. The Author of the paper assesses the degree to which in 2004–2006 Poland made use of the ESF financial resources under ‘Measure 1.4’ of the Sectoral Operational Programme for Human Resources Development. It is EFS funds and other EU resources that may, at least partially, prevent numerous problems. This may be achieved by the organization of vocational training and psychology workshops for people with disabilities and for those who collaborate with them.